Nanotechnological strategies to increase the oxygen content of the tumor - Zhang, Junjie; Tang, Kaiyuan; Fang, Runqi; Liu, Jiaming; Liu, Ming; Ma, Jiayi; Wang, Hui; Ding, Meng; Wang, Xiaoxiao; Song, Yanni; Yang, Dongliang (Frontiers in Pharmacology, 2023)
Hypoxia is a negative prognostic indicator of solid tumors, which not only changes the survival state of tumors and increases their invasiveness but also remarkably reduces the sensitivity of tumors to treatments such as radiotherapy, chemotherapy and photodynamic therapy, which have a severe dependence on oxygen. Thus, developing therapeutic strategies to alleviate tumor hypoxia has recently been considered an extremely valuable target in oncology. In this review, nanotechnological strategies to overcome hypoxia in tumor therapy in recent years are summarized，including (I) improving the hypoxic tumor microenvironment, (II) oxygen delivery to hypoxic tumors, and (III) oxygen generation in hypoxic tumors. Finally, the challenges and prospects of nanomaterials for alleviating tumor hypoxia are presented.